Psychosocial problems in children with thalassemia and their siblings - Louthrenoo O. (2014)
Beta-thalassemia is a chronic illness causing serious symptoms to children and a burden to families. The purpose of this study was to evaluate psychosocial problems in children with thalassemia and their siblings by using a semi-structured interview and the Pediatric Symptom Checklist (PSC). The study sample included 82 children with thalassemia, 20 siblings, and 50 control children without a chronic illness. With children and families demographically controlled, psychosocial problems were significantly more common in children with thalassemia than in those without chronic illness, 28.05 per cent vs 4 per cent (p=0.001), but there was no difference between siblings and the controls, 5 per cent vs 4 per cent (p=0.64). The mean PSC score in children with thalassemia was higher than that in the sibling and control group (18.34 vs 10.95 and 10.28, respectively; p<0.001). These findings suggest an increased risk of psychosocial problems in children with thalassemia that psychosocial intervention may be required to prevent major psychiatric disorders.